To switch or not to switch? Understanding German consumers' willingness to pay for green electricity tariff attributes - Saramena Sauthoff; Michael Danne; Oliver Mußhoff (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2017)
In order to achieve an environmentally friendly and sustainable energy supply, it is necessary that this goal is supported by society. In different countries worldwide it has been shown that one way consumers want to support the energy transition is by purchasing green electricity. However, few people make the leap from their intention to a buying decision. This study explores parameters that influence whether German consumers decide to switch to a green electricity tariff. We conducted a quota-representative online survey including a discrete choice experiment with 371 private households in Germany in 2016. For the econometric analysis, a generalized multinomial logit model in willingness to pay (WTP) space was employed, enabling the estimation of WTP values to be as realistic as possible. The results show that consumers' decision regarding whether or not to make the switch to green energy is influenced by many underlying drivers, such as the source of green energy, whether a person can outsource the switching process, and a person's attitude towards the renewable energy sources levy that currently exists in Germany. Implications for policy makers and recommendations for the marketing of green energy tariffs are provided.
Keywords: 330; energy transition; green energy; tariff switch; discrete choice experiment; generalised multinomial logit model; WTP space